Effect of Diabetic Foot Exercise on Foot Sensitivity and Blood Glucose Levels among Patients with Type 2 Diabetes Mellitus: A Quasi-Experimental Study in Primary Health Care - Vidia Khoirun Nisak; Handono Fatkhur Rahman; S. Tauriana (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2026)
Background: Diabetic neuropathy and poor glycemic control remain major complications among patients with type 2 diabetes mellitus (T2DM), contributing to decreased foot sensitivity and increased risk of diabetic foot ulcers. Non-pharmacological interventions, such as diabetic foot exercises, are considered effective strategies to improve peripheral circulation and glycemic control. However, evidence regarding their effectiveness in primary health care settings remains limited. Objective: This study aimed to analyze the effect of diabetic foot exercise on foot sensitivity and blood glucose levels among patients with type 2 diabetes mellitus. Methods: A quantitative quasi-experimental study with a one-group pretest–posttest design was conducted at Wangkal Community Health Center. The population consisted of 54 patients with T2DM, and 29 respondents were selected using total sampling based on inclusion criteria. Data on foot sensitivity were measured using a monofilament test, while blood glucose levels were assessed using a glucometer. Respondents participated in a structured diabetic foot exercise program for three consecutive days. Data were analyzed using the Paired t-test with a significance level of p < 0.05. Results: The findings showed a significant improvement in foot sensitivity after the intervention, with the mean score increasing from 10.52 to 14.72. In addition, the average blood glucose level decreased from 233.38 mg/dL to 195.03 mg/dL after the intervention. Statistical analysis indicated that diabetic foot exercise had a significant effect on improving foot sensitivity and reducing blood glucose levels (p = 0.000). Conclusion: Diabetic foot exercise is an effective non-pharmacological intervention to improve foot sensitivity and reduce blood glucose levels among patients with type 2 diabetes mellitus. The implementation of regular diabetic foot exercise is recommended as part of nursing interventions and community-based diabetes management in primary health care settings